Endocrine outcomes with proton and photon radiotherapy for standard risk medulloblastoma - Eaton, Bree R. (Neuro Oncol, 2016)
BACKGROUND: Endocrine dysfunction is a common sequela of craniospinal irradiation (CSI). Dosimetric data suggest that proton radiotherapy (PRT) may reduce radiation-associated endocrine dysfunction but clinical data are limited. METHODS: Seventy-seven children were treated with chemotherapy and proton (n = 40) or photon (n = 37) radiation between 2000 and 2009 with ≥3 years of endocrine screening. The incidence of multiple endocrinopathies among the proton and photon cohorts is compared. Multivariable analysis and propensity score adjusted analysis are performed to estimate the effect of radiotherapy type while adjusting for other variables. RESULTS: The median age at diagnosis was 6.2 and 8.3 years for the proton and photon cohorts, respectively (P = .010). Cohorts were similar with respect to gender, histology, CSI dose, and total radiotherapy dose and whether the radiotherapy boost was delivered to the posterior fossa or tumor bed. The median follow-up time was 5.8 years for proton patients and 7.0 years for photon patients (P = .010). PRT was associated with a reduced risk of hypothyroidism (23% vs 69%, P < .001), sex hormone deficiency (3% vs 19%, P = .025), requirement for any endocrine replacement therapy (55% vs 78%, P = .030), and a greater height standard deviation score (mean (± SD) −1.19 (± 1.22) vs −2 (± 1.35), P = .020) on both univariate and multivariate and propensity score adjusted analysis. There was no significant difference in the incidence of growth hormone deficiency (53% vs 57%), adrenal insufficiency (5% vs 8%), or precocious puberty (18% vs 16%). CONCLUSIONS: Proton radiotherapy may reduce the risk of some, but not all, radiation-associated late endocrine abnormalities.